(untitled) (Research, Society and Development, 2024)
Objective: To evaluate qualified prenatal care in primary care as a way of preventing obstetric violence in a high-risk maternity hospital. Methods: Descriptive, analytical and quantitative study with 36 postpartum women admitted to a high-risk maternity hospital who underwent prenatal care in primary care. Data was obtained through an interview with analysis of the pregnant woman’s card and application of a semi-structured questionnaire on sociodemographic and obstetric data, prenatal care in primary care according to Ministry of Health recommendations and identification and ways of preventing obstetric violence. Results: Regarding the identification of obstetric violence, a significant percentage (66.67%) of postpartum women reported at least one obstetric violence experienced during the care they received during childbirth. Knowledge of obstetric violence was moderately and highly significantly correlated with the adequacy of the start of prenatal care and weakly and significantly correlated with guidance on obstetric violence. Final considerations: It can be concluded that there is a correlation between the identification of obstetric violence and adequate prenatal care in terms of the number of consultations and prenatal guidance. Based on the visibility of cases, new strategies and policies can be developed to prevent obstetric violence.